A high-resolution method to assess cell multinucleation with cytoplasm-localized fluorescent probes. Issue 13 (27th May 2016) - Wen, Hui; Cui, Qinghua; Meng, Hui; Lai, Fangfang; Wang, Shufang; Zhang, Xiang; Chen, Xiaoguang; Cui, Huaqing; Yin, Dali
Abstract : Cell multinucleation is closely related to chromosomal instability. Abstract : Cell multinucleation is closely related to chromosomal instability. We report a simple, convenient method to assess cell multinucleation with cytoplasm-localized fluorescent probes (CLFP) which is superior to conventional nuclear staining methods. The CLFP method provides high-resolution images that enable the accurate calculation of the number of nuclear fragments.